Identification of gadoid species (Pisces, Gadidae) by sequencing and PCR-RFLP analysis of mitochondrial 12S and 16S rRNA gene fragments. - A. DI FINIZIO; G. L. RUSSO; GUERRIERO, GIULIA; CIARCIA, GAETANO (2007)
We applied PCR–RFLP (PolymeraseChainReaction – Restriction Fragment Length Polymorphism) analysis to identify seven gadoid species of different biogeographical origin and commercial relevance, namely Gadus morhua (Atlantic ocean); Trisopterus minutus capelanus, Trisopterus minutus minutus, Molva elongata, Phycis blennoides, Micromesistius poutassou (Atlantic ocean and Mediterranean sea); Theragra chalcogramma (Pacific ocean). Two DNA fragments belonging to mitochondrial 12S and 16S rRNA genes of about 430 and 630 bp, respectively, were isolated by PCR amplification. Their direct sequencing showed a significant genotypic diversity among gadoid species, useful for species identification. Digestion of 16S rRNA gene PCR fragment with MvaI or Bsh1285I restriction enzymes, followed by agarose gel electrophoresis of the cleaved products, yielded specific restriction profiles that enabled direct, visual identification of the species analyzed. This PCR– RFLP method allowed a clear and rapid discrimination of the gadoid species studied.